Embedding sustainable land-use optimization within system dynamics: bidirectional feedback between spatial and non-spatial drivers. (September 2022) - Azuara-García, Guadalupe; Palacios, Efrén; Montesinos-Barrios, Pilar
Abstract: In this paper, a space-time model is developed to support spatial planning. The temporal nature of the model allows the variables that condition land use to evolve periodically. In each time-step, land use allocation is optimized considering sustainability criteria. The model combines system dynamics techniques to simulate the evolution and interactions of economic and biophysical drivers using a multi-objective algorithm for spatial optimization that introduces bidirectional spatio-temporal feedback. It provides sets of maps for decision makers in which income and food self-sufficiency are maximized and the environmental impact of different what-if scenarios is minimized. The model has been applied in Los Llanos de San Juan (Mexico) for three scenarios: baseline, high and sustainable growth. The maps obtained by 2050 reduced water demand pressure by 1.4% and 4.7%, while crop production (in calories) was balanced with population food needs in 2035 and 2045 in the high and sustainable growth scenarios, respectively. Highlights: Time-space simulation in a single application for land use planning. Periodic bidirectionality between drivers and land response. Different simulation scenarios to inform discussion and decision-making. Food self-sufficiency and protection of water availability as territorial goals.